Freud and fundamentalism: the psychical politics of knowledge - Gourgouris, Stathis (Fordham University Press, 2010)
Annotation, At the heart of this volume are questions about the psychic components of the modes of thinking we call "fundamentalist" - that is, thinking that disavows multiplicities of meaning, abhors allegorical elements, and strives toward an exclusionary orthodoxy that codifies not just its own world but that of its adversaries, its others. The essays address transcendentalist orthodoxies of all kinds, whether religious or secularist. Fundamentalist elements in psychoanalysis itself are also placedin question, at the same time as psychoanalytic thinking and practice is explored as a mode of knowledge that ultimately unravels fundamentalist tendencies. The texts in this collection represent a wide array of disciplinary standpoints. Their overall aspiration is to interrogate discourses of orthodoxy, literalism, exclusion, and dogma - that is, discourses obsessed with monolithic (monolingual, monological, monolateral, monomythical, and certainly monotheistic) encounters with the world